2020
DOI: 10.1001/jamaophthalmol.2020.3154
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Coronavirus Disease 2019 Viral Material on Environmental Surfaces of an Ophthalmology Examination Room

Abstract: evere acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an enveloped, single-stranded RNA v i r u s t h a t c a u s e s c o r o n a v i r u s d i s e a s e 2 0 1 9 (COVID-19). 1 Person-to-person contact through droplets is believed to be the primary route of virus transmission. However, it has also been suggested that virus can be spread via contaminated surfaces. The survival of enveloped viruses, such as influenza, Middle Eastern respiratory syndrome coronavirus (MERS-CoV), and severe acute respirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 11 publications
1
30
0
Order By: Relevance
“…A laboratory study ( Van Doremalen et al, 2020 ) has explicated that viability of SARS-CoV-2 can last in aerosols for about 3 hr. In addition, this virus can be observed on dry surfaces for 8 to 72 hr, depending on the surface material ( Aytoğan et al, 2020 ; Carraturo et al, 2020 ; Van Doremalen et al, 2020 ). It is also reported that human coronaviruses SARS-CoV-2 remains on inanimate surfaces infectious for up to 9 days at room temperature ( Kampf et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A laboratory study ( Van Doremalen et al, 2020 ) has explicated that viability of SARS-CoV-2 can last in aerosols for about 3 hr. In addition, this virus can be observed on dry surfaces for 8 to 72 hr, depending on the surface material ( Aytoğan et al, 2020 ; Carraturo et al, 2020 ; Van Doremalen et al, 2020 ). It is also reported that human coronaviruses SARS-CoV-2 remains on inanimate surfaces infectious for up to 9 days at room temperature ( Kampf et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning their ability in adsorption, several results were positive for samples taken with these swaps. In addition to the surface materials, it can also be affected by other conditions, such as temperature and humidity, as well as existence of the condition for generating droplet or aerosol ( Aytoğan et al, 2020 ). It appears that the viability of SARS-CoV-2 on dry surfaces is identical to that of SARS-CoV-1 and MERS-CoV ( Chan et al, 2011 ; Rabenau et al, 2005 ; Van Doremalen et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the significant occupational risk associated with close exposure to potentially contaminated liquid droplets and particles, recommendations have been proposed and publicized so as to warrant professional and patient safety during ophthalmic examinations 86,120‐124 . These recommendations are continuously evolving, and should be adjusted according to the local context.…”
Section: Implications For the Ophthalmologistmentioning
confidence: 99%
“…Evidence exists of the ocular manifestations of coronavirus disease 2019 (COVID-19) and the presence of virus particles in ophthalmology examination rooms. [2][3][4][5] However, the risk of infection to health workers of caring for patients in such environments is yet to be established.…”
mentioning
confidence: 99%
“…There has been speculation about the risk to surgeons and others in the operating theatre during cataract surgery should the patient be harbouring the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). Evidence exists of the ocular manifestations of coronavirus disease 2019 (COVID‐19) and the presence of virus particles in ophthalmology examination rooms 2‐5 . However, the risk of infection to health workers of caring for patients in such environments is yet to be established.…”
mentioning
confidence: 99%